Measurement of the femoral neck anteversion angle using a three-dimensional reconstruction in the fixed coordinate system based on the basal anterior cortex of the femoral neck: an observational study - Ruibao Yang; Jie Lin; Guibin Han; Guangliang Jiang; Yingsheng Deng (BMC Surgery)
Abstract Purpose This study investigated the accessibility of 3D reconstruction in the fixed coordinate system(3D-R-FCS) based on the basal anterior cortex of the femoral neck in measuring the femoral neck anteversion angle (FNAA). Methods CT and EOS examinations were performed on 40 femoral samples synthesized by Sawbone. Two evaluators were responsible for measurement of the FNAA based on four different methods, including EOS 3D reconstruction, 3D-R-FCS, Reikerås, and Murphy methods. Results Measurement of the FNAA based on EOS, 3D-R-FCS based on the basal anterior cortex of the femoral neck, and the Reikerås and Murphy methods were 6.53°±4.28°, 7.08°±4.58°, 3.03°±4.44°, and 11.9°±4.91°, respectively. No statistical difference was detected for the FNAA measurements between EOS and the 3D-R-FCS based on the basal anterior cortex of the femoral neck (P > 0.05). However, a statistical difference was detected between the Reikerås and Murphy methods and EOS (P < 0.05). The value of the ‌intraclass correlation coefficients (ICCs) for the 4 methods measured by evaluator A were 0.89, 0.99, 0.75, and 0.81, respectively, while the ICCs measured by evaluator B were 0.91, 0.98, 0.71, and 0.79, respectively. The correlation coefficients between the two evaluators were 0.89, 0.99, 0.75, and 0.83, respectively. Conclusion The consistency of the scores for the FNAA measurement based on the 3D-R-FCS within and between the evaluators was the highest among the four methods and correlated well with the EOS measurement, which may potentially provide a more stable method for the measurement in clinical practice. Clinical trial number Not applicable.